Uncovering the spectrum of orthostatic hypotension in athletes with spinal cord injury: Implications for diagnosis, classification, and performance - Sobeeh, M. G.; Malik, R. N.; Thordarson, T.; Currie, K. D.; Hubli, M.; West, C. R., Sachdeva, R.; Krassioukov, A. (Medicine & Science in Sports & Exercise, 2026)
Background: Orthostatic hypotension (OH) is classified into three subtypes based on when blood pressure drops during an orthostatic challenge: initial (IOH; within <15 s), classic (COH; within 3 min), and delayed (DOH; after 3 min). These subtypes have varying degrees of sympathetic dysfunction. OH subtypes have not been characterized after spinal cord injury (SCI), potentially leaving many undiagnosed. This study determined the prevalence and severity of autonomic impairment across OH subtypes in SCI athletes.